THE IMPLICATIONS OF LEGAL CULTURE IN LAW ENFORCEMENT BY JUDGES ON JUSTICE PERSPECTIVE - Angkupi, Prima; Taufiq, Muhammad Shofwan (Jurnal Pembaharuan Hukum, 2024)
This study aims to examine the relationship between judges' legal culture and its implications for justice in law enforcement in Indonesia, judges' legal culture includes values, beliefs, norms and practices that influence judges' decision-making in the judicial process and the implications of this judges' legal culture can have a significant impact on justice in the justice system. This research uses normative legal research methods with a legislative approach and literature study, and uses descriptive analysis by applying the deductive method.  Legal culture greatly influences the way judges think and their decision-making. Judges' legal culture refers to the norms, values, and views they espouse in carrying out their duties as law enforcers. This includes how they view the law, justice, and their moral duties as judges.